Manifestations of violence in the novel Safiya's Tale by Laila Al Othman A Study in Feminist Criticism - Abdullah, Parwa Abdulqader Abdullah; Ali, Prof.Dr. Hazha Abas Ali (Sulaimani Journal for Humanities, 2025)
This study seeks to uncover manifestations of violence in the novel "Safiya's Tale," a feminist novel by Laila Al-Othman, from a feminist critical perspective. This study examines patterns of domestic violence, including verbal and physical violence, social violence, and symbolic violence to which women are subjected within the narrative structure. The character of the heroine, "Safiya," is a feminist model reflecting social oppression, as the novel focuses on the complex relationship between male authority and the female body as a space for control and violation. The study draws on feminist, psychological, and sociocultural approaches to analyze and interpret the patterns of oppression in the novel. It seeks to understand the relationship between violence and patriarchal authority, concluding that violence in the novel is not merely a tool of domination, but rather a catalyst for rebellion through storytelling.
Keywords: Feminist Criticism; Domastic violence; social violence; Symbolic violence